Decoding workplace gaslighting: evaluating a Persian version of the gaslighting workplace scale - Reza Ghanei Gheshlagh; Kimia Bigdeli; Priyam Kukreja; Jatin Pandey; Asra Nassehi; Mojtaba Jafari (BMC Nursing)
Abstract Background Gaslighting is a form of psychological abuse that undermines individuals’ perception of reality through manipulation and often exploits power imbalances in relationships. This phenomenon is prevalent in nursing workplaces, where subtle bullying behaviors persist. This study aims to evaluate the psychometric properties of the Persian version of the Workplace Gaslighting Scale in nursing context. Methods This cross-sectional study was conducted online in 2025 on 306 nurses. The Gaslighting in the Workplace scale was translated using the forward-backward method. Validity (face, content, construct, convergent, and discriminant) and internal consistency were assessed. Confirmatory factor analysis (CFA) was conducted using fit indices, while reliability was assessed with Cronbach’s alpha and McDonald’s omega. Data analysis was conducted using Amos 26 and Jamovi 2.4.14. Results The two-dimensional model of the scale was tested and confirmed with good fit indices in confirmatory factor analysis: CMIN = 121.627, DF = 53, CMIN/DF = 2.295, CFI = 0.960, TLI = 0.915, SRMR = 0.036, and RMSEA = 0.065. Cronbach’s alpha (0.911) and McDonald’s omega (0.912) confirmed excellent internal consistency. Most factor loadings were above 0.65, except for items 3 and 4. Convergent validity was partially supported (AVE: 0.434, 0.560; CR > 0.70). Discriminant validity was confirmed (HTMT: 0.695, MSV: 0.425). Conclusion The Persian version of the Workplace Gaslighting Scale demonstrated strong psychometric properties, including excellent construct validity and internal consistency, confirming its reliability for assessing gaslighting in nursing workplaces.